THE LEGAL AUTHORITY CHANGES OF THE CENTRAL BANK OF THE RUSSIAN FEDERATION IN DIGITAL ECONOMY SPHERE: PUBLIC AND PRIVATE ASPECTS - Pastushenko, Elena; Zemtsova, Larisa; Neverova, Nataliya; Malykhina, Elena (Revista Inclusiones, 2021)
In this article, the authors analyze the public and private law aspects of the changes in legal authority of the Central Bank of the Russian Federation as a financial market regulator within the digital economy development, based on the concept of the Bank of Russia legal acts in the system of the Bank of Russia legal, normative, law-enforcement, interpretive (acts of interpretation) and the contractual acts of Bank of Russia. There is an influence of the Bank of Russia program legal acts on strengthening the rule of law in the financial market, maintaining a proper level of law and order, and creating a trusted financial services environment, including digital forms. The research highlights the law-forming function of the Bank of Russia program legal acts in connection with the conceptual nature of normative, law-enforcement, interpretative, and contractual acts of the Bank of Russia. The author emphasizes the strategic nature of the Bank of Russia program legal acts, which are proposed to be considered as strategic planning acts. In order to fill the gap in legal regulation, it is proposed to affirm the legislative powers of the Bank of Russia to issue program legal acts in the field of financial technology development and in the field of ensuring financial accessibility and improving consumers’ financial literacy, which are currently issued by the Bank of Russia on an initiative basis. The article proves the hypothesis that Bank of Russia regulations can be issued not only in the sphere of public relations, but also in private sphere. The authors used dialectical, formal-legal, comparative-legal, as well as inductive methods of studying the changes in legal authority of the Central Bank of the Russian Federation in the economy digitization.